To Study of International Marketing Function in Global Company as Strategic Policy (International Journal of Food and Nutritional Sciences, 2022)
T his study ex am ine s the sig nific ance o f internatio nal m arke ting in the strateg ie s o f m ultinatio nal c orpo rations, w ith a p articular em phasis on the co nseq uence s of cultural adap tation, m arket loc alizatio n, and reg ulato ry ad herenc e. T he rese arc h m ake s use o f A N O V A , line ar m ultiv ariate regre ssio n analysis, as w ell as q uantitativ e and qualitativ e data co lle ctio n m e tho ds. A n analysis of the ex isting literature re ve als de ficienc ies in our unde rstand ing of the g lo bal m arketing strate gies e m p loye d by e nte rp rise s in d ev elop ing m arke ts. Initial results indic ate that c ultural adap tation, m arke t loc alizatio n, and reg ulatory com p liance are all sig nificantly and positive ly assoc iate d w ith the o ve rall succ ess o f m ultinational co rp oratio ns. T he p ape r disc usses the e thical co nside rations and lim itatio ns assoc iated w ith glo bal m arke ting. T he study e nhanc es the o ve rall co m prehe nsio n o f the ro le of internatio nal m arke ting in the co nte xt of the glo bal business strateg y of the org anizatio n.